Political opportunities, social movements and democratization - Coy, Patrick G. (Research in social movements, conflicts, and change, 2001)
As political opportunities shift, social movement decline or mobilization may result. The first section of this intriguing volume examines this phenomenon in depth while also moving theory-building forward. Significant contributions are made to collective identity theory, stalemate theory, and political process theory. This volume's concentration on political opportunity and social movements is accomplished through a focused series of papers that include case studies of specific social movements, comparative case studies of social movements, and comparative case studies of transnational issue networks. They include movements including the U. S. anti-nuclear power movement, the Rastafarians, the alternative and complimentary medicine movement, indigenous rights movements in Panama and Brazil, the animal rights movement, the anti-apartheid movement in South Africa, and the housing reform movements in post-Soviet Union Moscow and Budapest. A shorter, but no less important section closes this volume while taking up another historic focus of the series: social and political change. Here one paper documents democratization in Wales via the use of 'inclusive politics' by Plaid Cymru, another analyzes the use of 'political homicide' in Mexico during the 1990s, and a third explores campus unrest in the United States.